Answer:
That is a simplified as it can get.
Step-by-step explanation:
F(x) = k(x+2)(2x-1)(x-3), where k is some constant
= k(2x^3-3x^2-11x+6)
= k(-2x^3+3x^2+11x-6)
k defines some vertical stretch, so there are an infinitely many solutions for f(x).
I could help you in chat if you text me
1) Sundaes - $2 ; Banana Splits - $3
3x + 2(x+8) = 156
3x + 2x + 16 = 156
5x = 156 - 16
5x = 140
x = 28 banana split ; x + 8 = 28 + 8 = 36 sundaes
2) Palanzio's = 6.80 + 0.90x ; Guido's = 7.30 + 0.65x
6.80 + 0.90x = 7.30 + 0.65x
0.90x - 0.65x = 7.30 - 6.80
0.25x = 0.50
x = 2 number of toppings.
6.80 + 0.90x = 7.30 + 0.65x
6.80 + 0.90(2) = 7.30 + 0.65(2)
6.80 + 1.80 = 7.30 + 1.30
8.60 = 8.60
3) 6x - y = 4 ; y = 4x + 2
6x - (4x+2) = 4
6x - 4x - 2 = 4
2x = 4 + 2
2x = 6
x = 6/2
x = 3
y = 4x + 2
y = 4(3) + 2
y = 12 + 2
y = 14
6x - y = 4
6(3) - 14 = 4
18 - 14 = 4
4 = 4
Answer:
it would be the graph with the maximum (opening down) in the first photo with the top on the left side of the y axis